CONSORCIAÇÃO DE ALFACE E RÚCULA SOB DIFERENTES QUANTIDADES DE ESTERCO BOVINO - Ribera, Laura; De Moraes, Reginaldo; Coelho, Dener; Peres, Nathalia; Volpato, Tulio; Da Silva, Maiele Leandro (ANAIS DO ENIC, 2018)
-